Edukasi dan Praktik Permainan Tradisional Sebagai Upaya Pelestarian Sosial Budaya Anak Pesisir Pantai Amal Tarakan - Nurul Hidayat; Jumadi Jumadi; Eva Riana; Rindiani Rindiani; Ripka Ingan; Susan Nur Fadilla; Yeremia Anjasmara Riyanto (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This community service activity was conducted in Pantai Amal Village, Tarakan City, aiming to introduce and preserve traditional games that are increasingly neglected due to the dominance of gadgets among children. The program began with a brief socialization session on the importance of preserving traditional games in the digital era, followed by the practice of five traditional games: marbles, rubber jump, congklak, cabang, and bekel ball. Pre-test results showed that most children were unfamiliar with the rules and gameplay, while post-test results indicated a significant improvement in their understanding and ability to play. Children demonstrated great enthusiasm throughout the activity and even requested for future sessions. This program serves not only as entertainment but also as a medium to strengthen physical health, cognitive skills, social character, and local cultural preservation. Therefore, the activity contributes to maintaining socio-cultural identity in coastal communities and offers a relevant non-formal educational alternative.